2022
DOI: 10.1093/bjsopen/zrac142
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence on posthepatectomy liver failure: comprehensive review

Abstract: Introduction Despite important advances in many areas of hepatobiliary surgical practice during the past decades, posthepatectomy liver failure (PHLF) still represents an important clinical challenge for the hepatobiliary surgeon. The aim of this review is to present the current body of evidence regarding different aspects of PHLF. Methods A literature review was conducted to identify relevant articles for each topic of PHLF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 220 publications
(216 reference statements)
2
28
0
Order By: Relevance
“…Importantly, multivariate analysis revealed that CPT ≥ 120 min was an independent risk factor for PHLF in the open group, but not in the laparoscopic group. In the open group, remnant liver volume was the most relevant risk factor for liver failure, as previously reported [19, 25]. In this study, in the laparoscopic group, blood loss was an independent risk factor for PHLF in patients undergoing laparoscopic hepatectomy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Importantly, multivariate analysis revealed that CPT ≥ 120 min was an independent risk factor for PHLF in the open group, but not in the laparoscopic group. In the open group, remnant liver volume was the most relevant risk factor for liver failure, as previously reported [19, 25]. In this study, in the laparoscopic group, blood loss was an independent risk factor for PHLF in patients undergoing laparoscopic hepatectomy.…”
Section: Discussionsupporting
confidence: 81%
“…We identified risk factors for PHLF from previous studies and the results of this study. Thereafter, we selected covariates: age and sex as patient-associated factors, liver cirrhosis as liver-associated factors, and remnant liver volume and blood loss as surgery-associated factors [19]. Propensity scores were calculated for each patient using logistic regression analysis involving the five abovementioned factors.…”
Section: The Cut-off Value Of the Cumulative Pringle Timementioning
confidence: 99%
“…In recent years, immunotherapy and molecular targeting have gradually become hotspots of clinical and scientific research, R0 is still the main modality for the treatment of HCC and occupies an indispensable position. However, residual liver tissue regeneration is impaired after R0, and excessive apoptosis of liver cells will lead to the imbalance between liver regeneration and injury, resulting in ALF after hepatectomy[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver regeneration is a complex process that involves the proliferation of hepatocytes and the specific functions of numerous hormones, growth factors, and cytokines [ 60 , 61 ]. Post-hepatectomy liver failure (PHLF) continues to be a significant clinical challenge despite advances in hepatobiliary surgery over recent decades, and understanding the mechanism of liver regeneration after hepatectomy is essential to improving clinical outcomes [ 62 , 63 ]. Zabielski et al reported that the activity of acidic sphingomyelinase increased gradually from the 4th to 24th hour after partial hepatectomy in rats, accompanied by a significant increase in ceramide content and reduction in S1P content [ 33 ].…”
Section: Sphingolipid Metabolic Pathway In Liver Regenerationmentioning
confidence: 99%